Momengi Dan Perannya Sebagai Kontributor Utama Pengembangan Ekonomi Dusun Tumba Desa Pongongaila - mei Abd (AKASYAH: Jurnal Akuntansi, Keuangan dan Audit Syariah, 2021)
Momengi (corn farming) is the main occupation of the residents of Tumba Hamlet, Pongongaila Village, Pulubala District, Gorontalo Regency. Corn farming business can improve the economy of the community (farmers). In this study, researchers used a qualitative descriptive study by conducting explorative studies of the role of agricultural businesses in developing and improving the economy of the community (farmers). The results showed that agricultural business specifically requires human labor in one agricultural cycle so that this activity can open jobs for the community and improve the economy of Pongongaila Village. One agricultural cycle consists of: (1) the process of planting corn seeds (Molude), (2) the process of fertilization (2 times fertilization), (3) the process of spraying pests (2-3 times spraying), (4) the process of felling corn plants ( Totobu), (5) Stripping Process (Mongalipo), (6) The process of transportation from the highlands to the lowlands (Kijang), (7) The process of milling (molotori), (8) Transportation to the corn warehouse (last place).